2020
DOI: 10.1038/s41598-020-69522-w
|View full text |Cite
|
Sign up to set email alerts
|

Detectable HBV DNA during nucleos(t)ide analogues stratifies predictive hepatocellular carcinoma risk score

Abstract: Nucleos(t)ide analogs (NA) suppress hepatitis B virus (HBV) replication and reduce the risk of hepatocellular carcinoma (HCC). However, NA cannot suppress carcinogenesis completely in patients with chronic hepatitis B. The aims of this study were to identify risk factors for HCC and develop a refined carcinogenesis prediction model. Patients receiving NA therapy (n = 1,183) were recruited retrospectively from the 16 hospitals. All patients had been receiving NA continuously for more than 1 year until the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…In the time of NA administration was an excellent predictive model for carcinogenesis in Japanese population. 18 In the present study, the utility of these scores as a real-time monitor was verified by exam- We previously reported that undetectable HBV DNA during NA treatment is a predictive factor for HCC development, 19 and it was also confirmed in this cohort (data was not shown). Therefore, undetectable HBV DNA may be used as a factor constituting a predictive model for HCC development.…”
Section: Predictability Of Risk Models For Hcc Developmentsupporting
confidence: 69%
See 2 more Smart Citations
“…In the time of NA administration was an excellent predictive model for carcinogenesis in Japanese population. 18 In the present study, the utility of these scores as a real-time monitor was verified by exam- We previously reported that undetectable HBV DNA during NA treatment is a predictive factor for HCC development, 19 and it was also confirmed in this cohort (data was not shown). Therefore, undetectable HBV DNA may be used as a factor constituting a predictive model for HCC development.…”
Section: Predictability Of Risk Models For Hcc Developmentsupporting
confidence: 69%
“…Therefore, it is necessary to develop a model that reflects treatment response, and some factors may improve the predictability of HCC during NA treatment by combining PAGE‐B. We previously reported that undetectable HBV DNA during NA treatment is a predictive factor for HCC development, 19 and it was also confirmed in this cohort (data was not shown). Therefore, undetectable HBV DNA may be used as a factor constituting a predictive model for HCC development.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In our study of patients treated with antiviral therapy for more than 6 mo, the number of HBV DNA-negative patients in the HCC group was lower than that in the No-HCC group. Many studies have found a correlation between serum HBV DNA levels and the occurrence of HCC in patients with hepatitis B. Kaneko et al [ 39 ] reported that detectable HBV DNA was significantly associated with a higher risk of HCC development compared with continuously undetectable HBV DNA. Chen et al [ 40 ] found that the incidence of HCC increased with serum HBV DNA level at study entry in a dose-response relationship ranging from 108/100,000 person-years for an HBV DNA level of < 300 copies/mL to 1152/100,000 person-years for an HBV DNA level of 1 million copies/mL or more.…”
Section: Discussionmentioning
confidence: 99%
“…This classification achieved a negative predictive value of 99.5% in excluding patients without HCC development at 5 years. However, the persistent presence of detectable HBV DNA during NUC therapy is associated with HCC development [ 71 ], leading to the development of the new PAGE-B-DNA score. The latter combines features of the PAGE-B algorithm with the level of detected HBV DNA and has proven to be efficient in refining HCC risk stratification.…”
Section: Hcc Risk Scoring Systems In Controlled Patients Infected mentioning
confidence: 99%